2018
DOI: 10.1002/adma.201801885
|View full text |Cite
|
Sign up to set email alerts
|

Full Electric Control of Exchange Bias at Room Temperature by Resistive Switching

Abstract: Electric control of exchange bias (EB) is of vital importance in energy-efficient spintronics. Although many attempts have been made during the past decade, each has its own limitations for operation and thus falls short of full direct and reversible electrical control of EB at room temperature. Here, a novel approach is proposed by virtue of unipolar resistive switching to accomplish this task in a Si/SiO /Pt/Co/NiO/Pt device. By applying certain voltages, the device displays obvious EB in the high-resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 42 publications
(43 reference statements)
2
45
2
Order By: Relevance
“…The ON/OFF ratio achieves ≈10 5 . Note that an apparent high quality bipolar RS character is realized by adding a HfO x layer between CoO x and Pt electrode, which is different from previously reported unipolar CoO x and NiO x ‐based RRAM . It is because RS devices with HfO x dielectric layer generally show a bipolar switching behavior .…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…The ON/OFF ratio achieves ≈10 5 . Note that an apparent high quality bipolar RS character is realized by adding a HfO x layer between CoO x and Pt electrode, which is different from previously reported unipolar CoO x and NiO x ‐based RRAM . It is because RS devices with HfO x dielectric layer generally show a bipolar switching behavior .…”
contrasting
confidence: 62%
“…Resistive random access memory (RRAM), which shows low and high resistance states (LRS and HRS) by the formation and rupture of conductive filaments in metal/insulator/metal sandwich structure, is supposed to be one of promising candidates for the next‐generation nonvolatile memories . Recently, the reversible control of magnetism in resistive switching (RS) structure with magnetic storage medium has been extensively explored . The spin transport is switched ON/OFF when the RRAM is at low/high resistance states .…”
mentioning
confidence: 99%
“…In comparison to solid‐state resistive switching‐based electric control by redox reactions in an AFM oxide via a top gate, in the present geometry, a metal AFM is at the bottom while the FM layer is covered by a native oxide, both of which are manipulated via the top gate. In this geometry, the redox processes are decoupled from the AFM/FM interface, and in consequence, the electric manipulation becomes independent of the AFM properties.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, temperature instead of voltage was used as a control parameter. First attempts to voltage‐control EB via ionic mechanisms involve topographically patterned elements consisting of a cobalt layer in contact with a CoO x or HfO x AFM layer that exhibits resistive switching . The voltage‐dependent EB is interpreted based on a resistive switching mechanism, involving the formation and rupture of conducting filaments in the AFM and associated dynamic atomistic rearrangement of the AFM/FM interface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that the perpendicular exchange coupling across the ferromagnetic/antiferromagnetic interface can influence both the coercivity and the PMA of a ferromagnetic sublayer in permalloy/CoO,22 CoPt/CoO,23 Co/CoO,24,25 and Fe/Mn26 systems. This provides a powerful platform for tailoring PMA as well as realizing emergent voltage‐controlled functionalities 27,28. In this work, interfacial exchange coupling of magnetic moments between ferromagnetic metal and antiferromagnetic oxides is used as an extra source to stabilize the perpendicular magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%